Influência das rotas de processamento na mesotextura e propriedades mecânicas da superliga de níquel 718 - Medeiros, Melânea Almeida Ramalho (2017)
The superalloy 718 is a precipitation hardened nickel-base alloy, commonly used for structural components that work under temperatures up to 650˚C and harsh environments, making this alloy widely used for airspace, offshore and nuclear components. This alloy is hardened mainly by precipitation of the phases γ” and γ’. Other phases can also precipitate, as primary carbides and δ phase. The thermomechanical processing may influence the presence and the volumetric fraction of these phases, crystallography of grain boundaries and their size. The grain boundary movement and consequent grain growth can be a limiting factor for applications where a grain size is a prime requisite. The aim of this work is to establish the dependence the processing routes for the control of grain size and, consequently, an increase in the fraction of Σ3n boundaries. Iterative processing routes have been developed combining cold deformation and recrystallization, inducing the formation of “special” low-energy boundaries (Σ<29) and the break of the connectivity of random boundaries (Σ>29). The characterization of the grain boundary character distribution was performed via EBSD analysis. The microstructural development of the alloy, especially the δ phase precipitation was observed by SEM. Tensile tests were performed in order to evaluate the influence of the microstructure on mechanical properties. The results show that a high proportion of Σ3n boundaries (> 60%) was achieved while maintaining a refined microstructure, via controlled precipitation of δ phase during processing. Regarding the mechanical properties, a positive relation of ductility with the amount of special boundaries was observed.